2020
DOI: 10.1108/jstpm-06-2019-0067
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation and novelty innovation: a study for Argentina

Abstract: Purpose This paper aims to analyse the influence of cooperation on the degree of novelty of technological innovations introduced by industrial firms in Argentina. This influence is analysed from three perspectives: cooperation by partner type [business partners or scientific and technological centres (S&T) partners]; cooperation by number of partner types, from no cooperation to cooperation with two partner types; and cooperation by goals pursued by firms. Design/methodology/approach The data come from o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 76 publications
(183 reference statements)
0
5
0
Order By: Relevance
“…From a sales perspective, it was found that extramural R&D investments increased the proportion of sales from high novelty products more than from low novelty products (Goméz, Salazar and Vargas, 2020). Pasciaroni and Barbero (2021) found that with growing amount of collaboration networks, level of novelty innovation grows. We adopted slightly different approach to rather answer the question whether extramural knowledge support emergence of both innovation of higher and lower level of novelty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a sales perspective, it was found that extramural R&D investments increased the proportion of sales from high novelty products more than from low novelty products (Goméz, Salazar and Vargas, 2020). Pasciaroni and Barbero (2021) found that with growing amount of collaboration networks, level of novelty innovation grows. We adopted slightly different approach to rather answer the question whether extramural knowledge support emergence of both innovation of higher and lower level of novelty.…”
Section: Discussionmentioning
confidence: 99%
“…The discussion on role of collaboration networks in case of emergence of innovations that are novel on different spatial levels can be considered just as emerging (Goméz, Salazar and Vargas, 2020;Pasciaroni and Barbero, 2021). This study is to our best knowledge the first to adopt the approach of classifying innovation novelty in relation to spatial levels (new to international, national, regional and local markets), which is in line with approaches used in Community innovation surveys (Knell and Srholec, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These companies need to cooperate to alleviate the scarcity of resources (Pasciaroni & Barbero, 2021). Cooperation requires trust (Arnold, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Many (Chesbrough, 2006). Existing literature provides evidence for the positive impact of open innovation, where a combination of internal and external knowledge and technology can help firms improve the innovation process (Belderbos et al, 2004;Bayona-Saez et al, 2017;Cheng and Huizingh, 2014;Laursen and Salter, 2006;Pasciaroni and Barbero, 2020;Van Beers and Zand, 2014). Among the determinant factors key to understanding R&D cooperation, the most relevant are firm size and intensity of innovation (Fritsch and Lukas, 2001).…”
Section: Gender Diversity and Open Innovationmentioning
confidence: 99%